Pelatihan Pijat Bayi Untuk Stimulasi Tumbuh Kembang Bayi Kepada Kelompok Kader Posyandu Di Puskesmas Pembantu Dalung Permai Wilayah Puskesmas Kecamatan Kuta Utara: Pelatihan Pijat Bayi Untuk Stimulasi Tumbuh Kembang Bayi Kepada Kelompok Kader Posyandu Di Puskesmas Pembantu Dalung Permai Wilayah Puskesmas Kecamatan Kuta Utara - Ni Putu Mirah Yunita Udayani; Ni Gusti Ayu Pramita Aswitami; Putu Ayu Dina Saraswati (Ahmar Metakarya: Jurnal Pengabdian Masyarakat, 2022)
Stunting is a health problem in children that can cause health problems, education and interfere with productivity in the future. Stunting toddlers tend to find it difficult to reach their good potential in physical and psychomotor growth and development. Various efforts have been made to overcome stunting, one of which is to stimulate growth and development through baby massage. The limited number of health workers causes the need for participatory activities by posyandu cadres to help train the community in baby massage. So that posyandu cadres must be equipped with the ability to do baby massage. The purpose of this community service is to provide knowledge and skills of baby massage to posyandu cadres. The method used is to provide training with the stages of preparation, implementation and evaluation. The results after being given baby massage training there was an increase in the knowledge and skills of posyandu cadres in doing baby massage.